2019
DOI: 10.1039/c9nr02738f
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved impurity-invisibility in graphene nanoribbons

Abstract: We investigate time-resolved charge transport through graphene nanoribbons supplemented with adsorbed impurity atoms. Depending on the location of the impurities with respect to the hexagonal carbon lattice, the transport properties of the system may become invisible to the impurity due to the symmetry properties of the binding mechanism. This motivates a chemical sensing device since dopants affecting the underlying sublattice symmetry of the pristine graphene nanoribbon introduce scattering. Using the time-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 97 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…We also confirmed that the overall picture of electron traversal times is not qualitatively changed by introducing an ac driving voltage compared to the response to a dc drive. Possible quantitative differences in the response signals to an ac drive could be related to signatures of photon assisted tunnelling on traversal time [ 37 , 65 ] but, for now, will be left for future work. On the other hand, it would also be interesting to consider, e.g., a short laser pulse for exciting the system out of equilibrium [ 90 , 91 , 92 ] instead of the quench of the voltage bias employed in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also confirmed that the overall picture of electron traversal times is not qualitatively changed by introducing an ac driving voltage compared to the response to a dc drive. Possible quantitative differences in the response signals to an ac drive could be related to signatures of photon assisted tunnelling on traversal time [ 37 , 65 ] but, for now, will be left for future work. On the other hand, it would also be interesting to consider, e.g., a short laser pulse for exciting the system out of equilibrium [ 90 , 91 , 92 ] instead of the quench of the voltage bias employed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that the traversal time has a clearer signature in AGNR than in ZGNR. This is because the charge densities in AGNR structures are more delocalised than in ZGNR, where the formation of standing-edge-state charge waves leads to wave fronts with a spatial orientation lying diagonal across the plane of the nanoribbon [ 35 , 36 , 37 ]. We also show that the effect of breaking chiral symmetry (on-site disorder) has less effect on the traversal times compared with the disorder that preserves chirality (hopping disorder).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2) and the dipole matrix elements at these energies. While these excitations around the MZMs are accessible by low-frequency driving, it is likely that larger-frequency laser-pulse excitation would bring about high-order harmonics of the basic driving frequency and corresponding mixing with the dipole-allowed transitions [60][61][62].…”
Section: B Laser-pulse Excitation and Transient Spectroscopymentioning
confidence: 99%
“…Recently, a time-dependent extension of the LB approach based on NEGF has been developed incorporating transient effects resulting from the switch-on of a bias, which may be an arbitrary function of time [67][68][69]. This time-dependent Landauer-Büttiker (TD-LB) method has been applied to the study of superconductivity [70,71], impurity models [72,73], double quantum dots [74], nanowires [75,76], energy currents [77][78][79], systems with spatial and dynamical disorder [30,80], time-dependent quantum noise and electron traversal times [30,81], and periodically driven molecular junctions [22]. In all these studies, the dynamical response of charge and current densities to external fields was computed.…”
Section: Introductionmentioning
confidence: 99%